Factors associated with HbA1c levels in poorly controlled type 2 diabetic patients in North-East Malaysia - A. Rahman, Nor Azlina; Ismail, Aziz al-Safi; Yaacob, Nor Azwany; Lin, Naing (Japan International Cultural Exchange Foundation (JICEF), 2008)
Objective: A study was conducted at all the health centres in Kelantan in North-East Malaysia to determine the common factors associated with poor controlled of type 2 diabetic patients. Design: A cross-sectional study Materials and Methods: A total of 208 patients with poor diabetic control (HbA1c levels of more than 6.5%) were selected by stratified random sampling from all health centres in Kelantan. Socio-demographic data, physical examination, and fasting blood were taken from the patients to determine the related associated factors using multiple linear regression. Results: The levels of HbA1c in the poorly controlled diabetic patients were significantly associated with fasting blood glucose (b=0.236, 95%CI=0.189,0.283), educational level (primary education: b=-0.965, 95%CI=-1.550,-0.380; secondary and tertiary education: b=-0.625, 95%CI=-1.228,-0.021), marital status (b=0.933, 95%CI=0.426,1.440) and patients receiving their care in health centres with Family Medicine Specialist (b=-0.495, 95%CI=-0.913,-0.076). Conclusion: Fasting blood glucose and being married were associated with higher levels of HbA1c, while having had formal education and receiving diabetic care in health centres with Family Medicine Specialist were associated with lower levels of HbA1c in poorly controlled type 2 diabetic patients in Kelantan.